1978
DOI: 10.1177/001440297804400606
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Achievement Tests: How Useful for Special Education?

Abstract: The extent and direction of curriculum bias in standardized reading achievement tests are examined. Bias was estimated by comparing the relative overlap in the contents of four separate reading achievement tests with the contents of five commercial reading series at first and second grade levels. Overlap between each achievement test and each reading series is reported in terms of achievement test grade equivalent scores that would be expected given mastery of the words that appear both as content in a reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(42 citation statements)
references
References 1 publication
0
40
0
2
Order By: Relevance
“…In educational psychology, there has been a move away ft^om a diagnostic formal assessment system towards a more functional assessment of students' skills (Rosenfield & Kuralt, 1990). Results attained by various standardized achievement tests have been found to vary depending upon foe test's match to foe curriculum being used for teaching (Jenkins & Pany, 1978). This shift is motivating educators to develop assessment methods which link assessment such as curriculum based measurement (CBM), a standardized version of curriculum based assessment, to classroom practice (Fuchs, Fuchs, & Hamlett, 1994).…”
Section: Relative Age Within Gradementioning
confidence: 99%
See 1 more Smart Citation
“…In educational psychology, there has been a move away ft^om a diagnostic formal assessment system towards a more functional assessment of students' skills (Rosenfield & Kuralt, 1990). Results attained by various standardized achievement tests have been found to vary depending upon foe test's match to foe curriculum being used for teaching (Jenkins & Pany, 1978). This shift is motivating educators to develop assessment methods which link assessment such as curriculum based measurement (CBM), a standardized version of curriculum based assessment, to classroom practice (Fuchs, Fuchs, & Hamlett, 1994).…”
Section: Relative Age Within Gradementioning
confidence: 99%
“…Concerns about the need for change from standardized measures which are costly and of limited utility are supported by research such as that done by Jenkins and Pany (1978) who analyzed correlations between five reading series and four standardized tests. They found that student achievement in a particular curriculum may not be reflected in that student's standardized test scores.…”
Section: Evidence In Favour Of Curriculum Based Measurementmentioning
confidence: 99%
“…The achievement that is most appropriate for use is the one that is the best match with the instructional objectives of the particular school "system" (Aiken, 2000). Although reviews of the group standardization sample demonstrate adequate reliability and validity coefficients for screening academic performance (Ebel, 1978;Wright, 1988), the content and administration procedures of the group achievement tests may not be a valid assessment of students educated exclusively in an individualized curriculum (Cizek, 1988;Jenkins & Pany, 1978;Wright, 1988). These measures were designed to assess and compare the achievement of large groups (Cizek, 1991;Cizek & Ray, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Good and Salvia (1988) examined the curriculum bias effect for four achievement tests across third and fourth grades for Allyn and Bacon's Pafilfinder reading program. Using procedures identical to Jenkins and Pany (1978) and Webster et al (1985) to compute redundancy scores, they then converted these scores to standard scores based on each test's standardized norms. They found that the highest standard scores at third grade were generated using the Wide Range Achievement Test (WRAT), whereas the Peabody Individual Achievement Test (PIAT) had the highest scores at the fourth grade.…”
mentioning
confidence: 99%